2005
DOI: 10.1103/physrevb.71.104528
|View full text |Cite
|
Sign up to set email alerts
|

Field-tuned quantum critical point inCeCoIn5near the superconducting upper critical field

Abstract: We report a systematic study of high magnetic field specific heat and resistivity in single crystals of CeCoIn5 for the field oriented in the basal plane (H ab) of this tetragonal heavy fermion superconductor. We observe a divergent electronic specific heat as well as an enhanced A coefficient of the T 2 law in resistivity at the lowest temperatures, as the field approaches the upper critical field of the superconducting transition. Together with the results for field along the tetragonal axis (H c), the emerg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
91
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 28 publications
(57 reference statements)
14
91
1
Order By: Relevance
“…Lowtemperature transport [9,32] and specific heat [10] studies have revealed a magnetic field-tuned QCP, with a critical field H that anomalously coincides with H c2 , the upper critical field for superconductivity. The pinning of H to H c2 was subsequently shown to hold regardless of field orientation [11] or suppression of the superconducting state by impurities [12], suggesting a novel form of quantum criticality closely linked with the superconducting state. Recent work has revealed other examples of systems that appear to have a field-tuned QCP pinned to H c2 , including cuprates [13,14] and iron pnictides [15].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Lowtemperature transport [9,32] and specific heat [10] studies have revealed a magnetic field-tuned QCP, with a critical field H that anomalously coincides with H c2 , the upper critical field for superconductivity. The pinning of H to H c2 was subsequently shown to hold regardless of field orientation [11] or suppression of the superconducting state by impurities [12], suggesting a novel form of quantum criticality closely linked with the superconducting state. Recent work has revealed other examples of systems that appear to have a field-tuned QCP pinned to H c2 , including cuprates [13,14] and iron pnictides [15].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…16) It has been stressed 17) that because the superconducting transition is first order, a QCP right at H c2 (0) could not originate from the superconducting transition, but explaining the coincidence of a magnetic QCP with H c2 (0) is by no way simple (see for example the discussion in ref. 18). …”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] It is expected that this AFM order will be closely related to the AFM quantum critical point observed in CeCoIn 5 . 28,29) Therefore, the nuclear magnetic resonance (NMR) 25,27) and neutron scattering 26) measurements may have uncovered a novel superconducting state in this strongly correlated electron system. In particular, the neutron scattering measurement has explored the properties of the AFM order and found that the wave vector of the AFM order is incommensurate q IC ¼ Q þ IC with IC along the ½1; À1; 0 direction for magnetic fields in the ab-plane of the tetragonal lattice.…”
Section: Introductionmentioning
confidence: 99%